The Impinge of the State of Emergency on the Fundamental Freedoms - Le Teno, Sandrine (USFQ Law Review, 2017)
This article is about the state of emergency in France, which will be in force until the 15th July 2017. After explaining the previous declaration of the state of emergency and its consequences, the article points out the conflict between the declaration of the state of emergency in France and fundamental freedoms as they are enshrined in French Law (law of 3rd April 1955 and law of 20th November 2015) as well as European (European Convention on Human Rights) and International (International Covenant on Civil and Political Rights) law and explains under which conditions the state of emergency can be lawful even if it implies a reduction or a derogation to fundamental freedoms which are supposed to be protected by the national and international pieces of legislation.
Keywords: France; State of emergency; Extension; Fundamental Freedoms; European Convention on Human Rights; International Covenant on Civil and Political Rights